Michael Faraday : - Williams, L. Pearce (Da Capo Press, 1987)
Michael Faraday's work has lasting influence on the everyday lives of everybody, not least in the form of batteries and electric motors. A true chemical physicist, his work pioneered the subject of electrochemistry, the understanding electricity and began the search for a unified field theory. This book describes his life and his work in a most readable manner. It can be used as a history of his contribution to science, or as a reference to his experiments and paper. More emphasis is given by the author to his work in physics than in chemistry, but nonetheless this is probably the best biography of one of the leading contributors to modern science.